2012
DOI: 10.1007/s00005-012-0205-y
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy, Apoptosis, Mitoptosis and Necrosis: Interdependence Between Those Pathways and Effects on Cancer

Abstract: Cell death is a fundamental ingredient of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(161 citation statements)
references
References 137 publications
(182 reference statements)
3
149
0
2
Order By: Relevance
“…Cell death in general occurs by apoptotic, necrotic, autophagic, or additional mixed mechanisms (39). Like the extensive degeneration of PNs in young nr-mutant mice, we found selective death of PNs in P20 tPA-injected WT cerebella ( Fig.…”
Section: Cell Death Caused By Excess Tpa Via Abnormal Mitochondria Andsupporting
confidence: 53%
“…Cell death in general occurs by apoptotic, necrotic, autophagic, or additional mixed mechanisms (39). Like the extensive degeneration of PNs in young nr-mutant mice, we found selective death of PNs in P20 tPA-injected WT cerebella ( Fig.…”
Section: Cell Death Caused By Excess Tpa Via Abnormal Mitochondria Andsupporting
confidence: 53%
“…42,43 The mTOR pathway can form 2 multiprotein complexes with distinct functionalities: mTORC1 (leads to Akt inhibition) and mTORC2 (leads to Akt activation). Phoshorylated Akt induces mTORC1 activation through intermediate molecules and Akt itself is phoshorylated by the mTORC2 complex.…”
Section: Discussionmentioning
confidence: 99%
“…We found that free CQ significantly increased LC3-II expression in A549/T and A2780/T cells in a concentration-dependent manner, and this inhibition effect also occurred when CQ was co-encapsulated with PTX in liposomes ( Figure 5). Therefore, liposomal CQ could still act as a sensitizer to enhance PTX-induced apoptosis 36,37 and cytotoxicity in A549/T and A2780/T cells ( Figure 2; Table 2). These results show that A549/T cells were more sensitive to the treatment with PCL preparations compared to A2780/T cells.…”
Section: Discussionmentioning
confidence: 99%